PELATIHAN PEMBUATAN ALAT CUCI TANGAN TIPE PEDAL SEBAGAI FASILITAS PENCEGAHAN COVID-19 DI TEMPAT IBADAH KELURAHAN SUPRAU - andreas pujianto; M. Zaki Latif Abrori; Sigit D. P. Sidhi; Akhmad Nurfauzi; Djoko Prasetyo; Rezza Ruzuqi (Politeknik Kelautan dan Perikanan Sorong, 2021)
Handwashing tool is one of the facilities that must be provided by places of worship as an effort to implement health protocols to prevent the spread of Covid-19. This community service aims to provide knowledge and skills to worshipers in places of worship to make handwashing tools independently. Service activities are carried out by providing training on the manufacture of pedal-type handwashing tools so that they can be applied at the GKI Immanuel church and the Nurul Salam mosque, Supra Village, Sorong City. The theory and practice of making handwashing tools were given to training participants at the Manufacturing Workshop, Politeknik Kelautan dan Perikanan Sorong. Pre and post-tests are used to evaluate the implementation of the training. The number of correct answers to the pre and post-test questions given to participants increased from 12.86% to 82.86%.